1985
DOI: 10.1007/bf01065653
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of racemic warfarin in adult patients

Abstract: The population pharmacokinetics of racemic warfarin was evaluated using 613 measured warfarin plasma concentrations from 32 adult hospitalized patients and 131 adult outpatients. Warfarin concentrations were measured in duplicate using a high-performance liquid chromatographic procedure. The pharmacokinetic model used was a one-compartment open model with first-order absorption (absorption rate constant set equal to 47 day-1) and first-order elimination. The extent of availability was assumed to be one. A line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
42
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(51 citation statements)
references
References 21 publications
8
42
1
Order By: Relevance
“…The effect of smoking (ϩ 20.1%) was larger than expected, since hepatic enzyme induction from smoking results in only a 10% increase in warfarin clearance. 29 Directionally, however, this is consistent with other For personal use only. on May 9, 2018. by guest www.bloodjournal.org From studies that have shown a significant relationship between smoking status and warfarin dose.…”
Section: Discussionsupporting
confidence: 85%
“…The effect of smoking (ϩ 20.1%) was larger than expected, since hepatic enzyme induction from smoking results in only a 10% increase in warfarin clearance. 29 Directionally, however, this is consistent with other For personal use only. on May 9, 2018. by guest www.bloodjournal.org From studies that have shown a significant relationship between smoking status and warfarin dose.…”
Section: Discussionsupporting
confidence: 85%
“…18 In keeping with the need for ease of use in clinical practice, a simplified algorithm with only a few variables can be very intuitive in application and easily implemented, which is particularly appealing to busy physicians practicing in community settings. In addition, a simple genotypebased algorithm may be used in conjunction with the traditional dose adjustment for patients on amiodarone, namely an additional 15% to 22% dose reduction, given its known correlation with therapeutic dose 20,31,32 ; or with a 10% dose escalation for smokers. 20 Until prospective studies provide solid evidence for the advantage of using a complicated dosing algorithm, simple guidance in dose adjustment based on genotyping information can be helpful options to physicians.…”
Section: Clinical Applicationmentioning
confidence: 99%
“…Such PK models address the underlying process of absorption, distribution, and elimination as model parameters, allowing for a better prediction. Population PK analyses resolve the observed variability into its interpatient and random assay within patient error components, but whereas these methods [13] have a long history of usage for the more common blood-clotting drugs, that is not the case with haemophilia treatments. Only recently a population analysis has been reported for factor VIII dose individualisation in healthy adults with haemophilia A before surgery [12,14].…”
Section: Introductionmentioning
confidence: 99%